Sensory Marketing (SMKT) and Consumer Buying Behaviour (CBB): A Focus on De-United Food Industry Limited - Iyadi, Rollins Chiyem; Ofili, Peter Nkeonyesua; Obieze, Ewere Success; Olannye, Henry Odigwe; Odeleye, Olayinka Tope (Journal of Ecohumanism, 2024)
This study examined sensory marketing (SMKT) and consumer buying behavior (CBB) with a focus on De-United Food Industry Limited. The design adopted for this study is the descriptive design. A descriptive research is a collection and interpretation of data. Information was collected by asking a good number of persons sampled from the population with known backgrounds on the questions. The population for this study consists of employees of De-United Food Industry Limited, Lagos State. For the purpose of this study based on the small population of 97 members, the research purposively adopted the population of 97 members as the sample size. The researcher used semi-structured questionnaire as the tools for obtaining the necessary information for the research. The questionnaire was made up of open-ended and closed-ended questions which were self-constructed. This study contributed to the existing body of knowledge in the fields of SMKT and consumer behavior, offering practical implications for businesses aiming to enhance their marketing efforts and customer satisfaction in the food industry. Ultimately, it is expected that this research will assist De-United Food Industry Limited in optimizing its SMKT strategies to better serve its customers and achieve sustainable growth in a highly competitive market. The study therefore recommends that customers allowed should be to touch and feel the products. Whether its clothing, electronics, or home goods, providing a hands-on experience can build trust and increase the likelihood of purchase. The Use of background music to set the mood and create a pleasant shopping environment is highly recommended as they affect the mood of customers. The tempo, volume, and genre should match the store's theme and customer expectations.